2022
DOI: 10.1007/s11468-022-01745-1
|View full text |Cite
|
Sign up to set email alerts
|

Optical Ammonia-Sensing Probe Based on Surface-Plasmon Resonance of Silver-Nanoparticle-Decorated Superparamagnetic Dendritic Nanoparticles

Abstract: Ammonia is a serious contaminant of aquaculture water due to its continuous release into the water environment during the biological processes of aquatic animals. Ammonia accumulation in water has negative environmental impacts, including eutrophication and the death of aquatic organisms. Therefore, sensitive and accurate determination of ammonia is an urgent need, especially in pisciculture systems. Here, we report the fabrication of a novel magnetic–hyperbranched nanomaterial-based ammonia-sensing probe for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Therefore, there is an urgent need for accurate, rapid, on-site and sensitive ammonia determination, especially in fish farming systems. 30 In this study, a colorimetric sensor was developed based on the specific dissolution of silver( i ) oxide by ammonia, which triggers the activation of silver ions and the subsequent formation of core/shell gold/silver NRs. This led to changes in the surface composition, size, and aspect ratio of the AuNRs, which were accompanied by vivid color changes in the solution from light green to red/orange.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there is an urgent need for accurate, rapid, on-site and sensitive ammonia determination, especially in fish farming systems. 30 In this study, a colorimetric sensor was developed based on the specific dissolution of silver( i ) oxide by ammonia, which triggers the activation of silver ions and the subsequent formation of core/shell gold/silver NRs. This led to changes in the surface composition, size, and aspect ratio of the AuNRs, which were accompanied by vivid color changes in the solution from light green to red/orange.…”
Section: Discussionmentioning
confidence: 99%
“…The detection limit of ammonia in the present study is lower than the reported methods. 1,[31][32][33][34][36][37][38][39] Most reports do not provide visual detection 1,[30][31][32][33][34]36,39 or clear color differentiation. 35,38 In the present study, the color changes of the sensor in the absence and presence of different ammonia concentrations are completely different and can be easily detected by the naked eye.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…Optical sensors are another type of sensor used for ammonia detection [18]. These sensors use the absorption or fluorescence of light to detect ammonia, making them highly selective and sensitive [19]. These sensors can also detect signals through changes in the light scattering pattern [20].…”
Section: Introductionmentioning
confidence: 99%
“…Optical sensors are another type of sensors used for ammonia detection [18]. These sensors use the absorption or fluorescence of light to detect ammonia, making them highly selective and sensitive [19]. These sensors can also detect signals through changes in light scattering patterns [20].…”
Section: Introductionmentioning
confidence: 99%